Ageing without dementia: can stimulating psychosocial and lifestyle experiences make a difference?. Issue 6 (June 2020) - Fratiglioni, Laura; Marseglia, Anna; Dekhtyar, Serhiy
Summary: In a world with an ageing population, dementia has become an urgent threat to global health and wellbeing. Psychosocial and lifestyle factors, such as higher socioeconomic positions, longer times spent in education, greater occupational complexity, reduced stress at work, and engagement in mental, physical, and social activities, have been hypothesised to supply resilience against dementia. Although questions remain surrounding the role of these factors in the development of dementia, scientific advancements have considerably expanded our understanding of modifiable psychosocial and lifestyle factors and their neuroprotective and compensatory influences over a life course. Evidence from observational studies is robust enough to suggest that stimulating psychosocial and lifestyle factors are protective against dementia. And, although the corresponding evidence from intervention studies is still scarce, public health campaigns promoting psychosocial and lifestyle factors might improve the health and wellbeing of people aged 60 years and older.